Avoid Ethical Misconduct in Manuscript Preparation. (January 2016) - Hicks, Rodney W.; Harris, Ruth
Abstract : In order for nurses and other health care professionals to make important contributions to the literature, there must be an awareness of the many areas where unintentional ethical conflicts can arise. Leading ethical concerns include plagiarism, duplicate submission, authorship standards, bias, and conflicts of interest. Although many sources are available on the variety of ethical concerns, this article takes the position to identify the area of concern and describe why it is an ethical violation. Solutions are posed for resolving the conflict, including why medical librarians can help in the publishing process.